TINGKAT LITERASI TEKNOLOGI INFORMASI KOMUNIKASI MASYARAKAT KOTA MAKASSAR - Juditha, Christiany (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2011)
Literacy level of Information and Communications Technology in society at the city of Makassar can be categorize as pretty good/high, because according from three ICTs media that had been researched which are, Computer, Internet, and cell phone, all of them had been used by most of respondents. The used of cell phone are the highest, followed by computer and Internet. The purposes of using ICT are to make it easier for communicating, working and acquiring information. This result will really help to succeed the process of City Governments program to make Makassar became a Cyber City.